2022
DOI: 10.1093/humrep/deac097
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyaluronic acid in embryo transfer media in donor oocyte cycles and autologous oocyte cycles: a systematic review and meta-analysis

Abstract: STUDY QUESTION Does the addition of hyaluronic acid (HA) to embryo transfer medium improve pregnancy outcomes in both autologous and oocyte donation IVF cycles? SUMMARY ANSWER The best available evidence indicates that the addition of HA to embryo transfer medium is clinically beneficial in cycles with autologous oocytes. WHAT IS KNOWN ALREADY There is a know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“… Heymann etal. (2022) later summarized the data separately for donor oocyte cycles and autologous oocyte cycles and concluded that, in donor oocyte cycles, HA addition showed little effect on LBR (RR 1.12; 95% CI 0.86 to 1.44; 2 RCTs; n = 317; I 2 = 50%; low-quality evidence) and CPR (RR 1.06; 95% CI 0.97 to 1.28; 3 RCTs; n = 351; I 2 = 23%; low-quality evidence).…”
Section: Resultsmentioning
confidence: 99%
“… Heymann etal. (2022) later summarized the data separately for donor oocyte cycles and autologous oocyte cycles and concluded that, in donor oocyte cycles, HA addition showed little effect on LBR (RR 1.12; 95% CI 0.86 to 1.44; 2 RCTs; n = 317; I 2 = 50%; low-quality evidence) and CPR (RR 1.06; 95% CI 0.97 to 1.28; 3 RCTs; n = 351; I 2 = 23%; low-quality evidence).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we show that hTSC NV HBEGF and NVs, enriched in these molecules, are effective supplements for promoting endometrial adhesion to trophectodermal cells and trophectodermal invasion into Matrigel (Figure 5). For example, they may be paired with clinically available supplements such as EmbryoGlue, a viscous embryo transfer media which minimises embryo mobility [111,112], supports embryo health [113], and which hyaluronan content promotes interactions with CD44 [114], purported to enhance implantation [112,115] and live birth [116][117][118][119] rates by 7%-9%. Like gelatin methacryloyl-rich hydrogels [120][121][122], they may serve to prolong the stability and function of NVs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a clinically available supplement beneficial to both embryo and endometrium is EmbryoGlue, a viscous, hyaluronan-rich media purported to marginally increase implantation [166,167] and live birth [168][169][170][171] rates by 7%-9% by minimising embryo mobility [167,172], supporting embryo health [173], and promoting initial embryo-endometrial attachment via hyaluronate-CD44 interaction [81]. Given its viscosity, EmbryoGlue may function similarly to gelatin methacryloyl-rich hydrogels used to prolong the stability and function of EVs [174][175][176], without immobilising the implanting embryo.…”
Section: Discussionmentioning
confidence: 99%